Investigation into the effectiveness of feed spacer configurations for reverse osmosis membrane modules using Computational Fluid Dynamics - Kavianipour, Omid; Ingram, Gordon; Vuthaluru, Hari (Elsevier BV, 2017)
© 2016 Elsevier B.V.Reverse osmosis operations for water treatment are usually energy intensive and responsible for most of the product price. Several studies used flow characteristics to compare different geometries of feed spacers, but these cannot completely explain the effectiveness of feed spacers for promoting mass transfer near membranes. A few recent studies introduced a concept (Spacer Configuration Efficacy, SCE) combining mass transfer and energy consumption, but SCE has been applied only to a limited extent. The present study uses 3-dimensional steady state Computational Fluid Dynamics with mass transfer to compare four channels with feed spacer configurations (Ladder-type, Triple, Wavy and Submerged) and an empty plain channel using SCE and other performance measures. In contrast to previous studies, a saturated concentration boundary condition is employed at the membrane surface and optimised meshing of the domain is discussed. Power law correlations for SCE and other performance measures developed from the simulation results enable quick evaluation of the spacers. Results indicated that the assumed saturated solute concentration at the membrane strongly affects the mass transfer coefficient. Based on SCE, the Wavy spacer configuration showed the highest performance for Re>120 among the obstructed geometries considered, while Ladder-type was better for Re<120.